Brain source localization using EEG signals - Jatoi, M.A. (CRC Press, 2014)
The human brain generates magnetic signals or electric current when certain parts of the brain are active. Localization of brain signal sources corresponds to the estimation of their location and orientation with a minimum squared error between the calculated and measured boundary potential. This process of source estimation, which is also known as the inverse problem, is helpful in understanding the physiological, pathological, mental, and functional abnormalities, and cognitive behavior of the brain. This understanding leads to specifications for diagnoses of various brain disorders such as epilepsy and tumors. The human brain anatomy is shown in Figure 4.1 1. Â© 2015 by Taylor & Francis Group, LLC.